Development of a portable micro-XRF spectrometer and its application for the characterization of ancient and historical metal alloys - Kantarelou, V.; Sokaras, D.; Zarkadas, Ch.; Karydas, A.-G. (HNPS Advances in Nuclear Physics, 2020)
A portable micro-XRF spectrometer utilizing X-ray optics (polycapillary X-ray lens) has been developed and applied for the characterization of the surface of ancient and historical metal alloys within the Mediterranean basin. The spectrometer has been fully characterized with respect to its spatial resolution, elemental excitation efficiency and sensitivity. A dedicated quantification algorithm was also developed, whereas new analytical procedures were explored towards the optimum implemen- tation of the technique in the field of conservation.